2018
DOI: 10.1111/1346-8138.14580
|View full text |Cite
|
Sign up to set email alerts
|

Rapid alteration of serum interleukin‐6 levels may predict the reactivity of i.v. cyclophosphamide pulse therapy in systemic sclerosis‐associated interstitial lung disease

Abstract: Systemic sclerosis (SSc) is an autoimmune disorder characterized by excessive extracellular matrix deposition. Although SSc-associated interstitial lung disease (ILD) is one of the most important complications as a cause of death in SSc, prediction factors of treatment reactivity in SSc-ILD are still unclear. To assess relationships between interleukin (IL)-6 and reactivity to treatment, we measured serum IL-6 levels in 23 of active SSc-ILD patients under i.v. cyclophosphamide (IVCY) therapy and 20 of stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…[ 17 ] Serum IL-6 levels can be also used as an evaluation index for the efficacy of cyclophosphamide in the treatment of SSc-ILD. [ 18 ] Studies have confirmed that IL-6 is involved in the pathogenesis of SSc. [ 19 ] Interleukin 6 is implicated in the process of pulmonary fibrosis by promoting the upregulation of collagen-related gene expression, promoting the proliferation and differentiation of fibroblasts and myofibroblasts, inhibiting T cell apoptosis, and regulating the balance of Th17 cells and Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Serum IL-6 levels can be also used as an evaluation index for the efficacy of cyclophosphamide in the treatment of SSc-ILD. [ 18 ] Studies have confirmed that IL-6 is involved in the pathogenesis of SSc. [ 19 ] Interleukin 6 is implicated in the process of pulmonary fibrosis by promoting the upregulation of collagen-related gene expression, promoting the proliferation and differentiation of fibroblasts and myofibroblasts, inhibiting T cell apoptosis, and regulating the balance of Th17 cells and Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is, therefore, a loop between the fibroblast and the B-cell that is partly dependent on IL-6. Noteworthy, IL-6 and IL-10 serum levels correlated with skin and pulmonary fibrosis ( 82 , 83 ). Otherwise, circulating B-cells secrete increased amounts of IL-8, IL-1β, BAFF, and CXCL13, which are proinflammatory, profibrotic cytokines or chemo-attractant molecules, both in scleroderma mouse models and SSc patients ( 20 , 22 , 37 , 84 ).…”
Section: Functional Characteristicsmentioning
confidence: 99%
“…29 The results of previous studies have shown that the level of IL-6 in the serum of SSc patients is higher than that of the healthy control group, and it may be related to the activity state, severity, and prognosis of the disease. 30,31 The correlation between IL-6 and clinical phenotypes can be affected by the course of the disease, sample size, and testing methods. Hasegawaet al found that serum IL-6 levels in patients with SSc fibrosis were lower than those in non-fibrotic patients.…”
Section: Discussionmentioning
confidence: 99%